2018
DOI: 10.1016/j.ihj.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional echocardiographic evaluation of mechanical dyssynchrony in systolic heart failure with narrow QRS complex

Abstract: 3DE confirmed significant dyssynchrony in >50% HF patients with narrow QRS as demonstrated by other imaging methods. 3D distribution patterns of asynchronous segments indicate possibility of left ventricular mechanics related reasons responsible for lack of CRT responsiveness, an observation that generates hypothesis on possible reasons of CRT non-responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…LVMD can occur with normal QRS, however, patients with BBB do not always exhibit LVMD. 18–20 Through RT-3DE, Bhambhani et al found that the frequency of LVMD was equivalent or even lower in patients with HF and LBBB compared to narrow QRS (47.8% vs 55.7%, P =NS), 19 which is similar to our results (33.3% vs 46.5%, P = NS). The decreased frequency of LVMD in our DCM group is most likely attributable to the difference in etiology.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…LVMD can occur with normal QRS, however, patients with BBB do not always exhibit LVMD. 18–20 Through RT-3DE, Bhambhani et al found that the frequency of LVMD was equivalent or even lower in patients with HF and LBBB compared to narrow QRS (47.8% vs 55.7%, P =NS), 19 which is similar to our results (33.3% vs 46.5%, P = NS). The decreased frequency of LVMD in our DCM group is most likely attributable to the difference in etiology.…”
Section: Discussionsupporting
confidence: 91%
“…The decreased frequency of LVMD in our DCM group is most likely attributable to the difference in etiology. The cases in the study by Bhambhani et al included a number of patients with ischemic cardiomyopathy (ICM) (46%), 19 whose LVMD status was theoretically more severe due to scars. A recent study using SPECT to evaluate LVMD in patients with LBBB and RBBB found that the prevalence of LVMD is significantly higher in patients with LBBB (85%) than in patients with RBBB (40%) ( P < 0.01), 20 which is contradictory to our findings; a significant number of patients with ICM (more than 40%) were included in this study, which confirmed that LV scar was an independent factor in predicting LVMD; they concluded that LVMD was correlated with LVEF but not QRS duration, and that LVMD predicted CRT response better than QRS duration, 20 which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest, the original article titled “Three-dimensional echocardiographic evaluation of mechanical dyssynchrony in systolic heart failure with narrow QRS complex” published in your esteemed journal 1 . The authors have used 12-segment systolic dyssynchrony index (SDI) and have chosen the cutoff value as > 10% “in accordance with the observations reported by the investigators who introduced and validated this parameter” (under methods, 2.2 echocardiography section).…”
mentioning
confidence: 99%